Growth data from a field trial of Quercus suber plants regenerated from selected trees and from their half-sib progenies by somatic embryogenesis - Celestino, Cristina; Fernandez-Guijarro, B.; Hernández, Inmaculada; López Vela, Dolores; Carneros, Elena; Jiménez García, Jesús; Cardo, L.; Alegre, Jesús; Toribio, Mariano (Acta Horticulturae, 2009)
The development of reliable clonal propagation technologies is a requisite for performing Multi-Varietal Forestry (MVF). Somatic embryogenesis is considered the tissue culture based method more suitable for operational breeding of forest trees. Vegetative propagation is very difficult when tissues are taken from mature donors, making clonal propagation of selected trees almost impossible. We have been able to induce somatic embryogenesis in leaves taken from mature oak trees, including cork oak (Quercus suber). This important species of the Mediterranean ecosystem produces cork regularly, conferring to this species a significant economic value. In a previous paper we reported the establishment of a field trial to compare the growth of plants of somatic origin vs zygotic origin, and somatic plants from mature trees vs somatic plants from juvenile seedlings. For that purpose somatic seedlings were regenerated from five selected cork oak trees and from young plants of their half-sib progenies by somatic embryogenesis. They were planted in the field together with acorn-derived plants of the same families. After the first growth period, seedlings of zygotic origin doubled the height of somatic seedlings, showing somatic plants of adult and juvenile origin similar growth. Here we provide data on height and diameter increases after two additional growth periods. In the second one, growth parameters of zygotic seedlings were also significantly higher than those of somatic ones, but there were not significant differences in height increase between seedlings and somatic plants of mature origin. In the third growth period, height and diameter increases of somatic seedlings cloned from the selected trees did not differ from those of zygotic seedlings, which were still higher than data from plants obtained from somatic embryos from the sexual progeny. Therefore, somatic seedlings from mature origin seem not to be influenced by a possible ageing effect, and plants from somatic embryos tend to minimize the initial advantage of plants from acorns.
Keywords: Cork oak; field establishment; forest improvement; rejuvenation; vegetative propagation; woody plant micropropagation

First data from a field trial of Quercus suber plants regenerated from mature selected trees and from their half-sib progenies by somatic embryogenesis - Celestino, C.; Hernández, I.; Lopez-Vela, D.; Carneros, E.; Alegre, J.; Toribio, M.; Fernandez-Guijarro, B.; Cardo, L. (Proceedings of the Second International Symposium on Acclimatization and Establishment of Micropropagated Plants, 2007)
Somatic embryogenesis is considered as the most suitable current regeneration technique for the conservation and genetic improvement of tree species. The ability to induce somatic embryogenesis in leaves from mature trees gives the possibility to compare the performance of the parent trees and their progenies at the same age and place of test. Somatic seedlings were regenerated from five selected cork oak trees and from young plants of their half-sib progenies. They were planted in the field conjointly with zygotic seedlings of these families, to test the comparisons somatic vs. zygotic origin and somatic from mature trees vs. somatic from juvenile seedlings. The effect of genotype and kind of progeny will be studied in a complete factorial design; therefore the field trial comprised 15 treatments arranged in five completely randomised blocks. Each experimental unit included three plants that were distributed following a row and column pattern. Fist survival and height data after six and twelve months of establishment are provided. All plants from seeds survived while almost the half of somatic seedlings died after the winter and they were replaced. Almost 70% of these plants survived after the following summer. There were no differences between somatic seedlings of mature or juvenile origin. Zygotic seedlings doubled the height of the somatic ones after one year in the field, and within these plants those of mature origin grew slightly more than those of juvenile source. Differences due to genotype and family effects were noticeable. No apparent morphological alterations were detected among the three kinds of tested progenies.
The following values have no corresponding Zotero field: periodical: Proceedings of the Second International Symposium on Acclimatization and Establishment of Micropropagated Plants issue: 748 pub-location: PO BOX 500, 3001 LEUVEN 1, BELGIUM
Keywords: Cork oak; field establishment; rejuvenation; Somatic embryogenesis; woody plant micro-propagation